Influence of geometry and slurry properties on fine particles suspension at high loadings in a stirred vessel - Ibrahim, S.; Wong, S.D.; Baker, I.F.; Zamzam, Z.; Sato, M.; Kato, Y. (Institution of Chemical Engineers, 2015)
Particle size, solids loading and impeller clearance from the base were all found to have significant effects on the just-suspension of fine particles in a stirred tank. At the higher end of particles size studied, where there is greater difference in settling velocities between particle sizes, the smaller the particles the less specific energy, ɛjs is required for just-suspension. But at the low end of particle size range, changes in the settling velocity are small while continued reduction in particle size corresponds to substantial increase in total particle surface area, leading to increased ɛjs possibly due to particles interactions. Just-suspension of PMMA particles of diameter 195.5 μm required higher ɛjs than for 75.3 μm particles, whereas ɛjs for 75.3 μm particles was lower than that for 18.0 μm diameter particles. Experiments were conducted in water in a 15.5 cm cylindrical tank at an aspect ratio of 1:1 over a range of loadings from 5 to 40% by weight. The HR100 and HS604 SUPERMIX® impellers manufactured by SATAKE, generally showed better efficiencies compared to the conventional 4 pitched-blade turbine and 3-blade propeller, in addition to being less affected by changes in operational parameters. The HS604 performance proved that a radial impeller can be comparable to or better than a downward axial impeller in solid–liquid suspension if used at very low clearance. S factor values under different experimental conditions are presented.